Assessment of Factor VII and Factor X - Shaw, S; Pegrum, G. D; Farthing, C. P; Wolff, S (Thrombosis and Haemostasis, 1966)
A method is described to separate factor VII from factor X in normal serum using electrophoresis in a polyvinyl chloride block. A potent source of factor X is obtained. This may be used in correction studies and for assessment of deficiencies of factor VII in patients.